Alberto Sdegno, Veronica Riavis (a cura di). (2023). DAI Il Disegno per l’Accessibilità e l’Inclusione. Alghero: Publica (diségno, 2024)
The physical and virtual practicability of spaces, combined with the possibility of taking advantage of information technologies related to the communication of goods and services, allows people with disabilities to access Cultural Heritage on an equal basis with other members of the social context. The research carried out in this field by Drawing has made it possible to teach the relationships between the various subjects to have a broader and more coordinated design vision of the aspects studied. [read more]